I.YUSUPOV SHÍǴARMALARÍNDA LIRIKALÍQ QAHARMANNÍŃ MILLIY XARAKTERIN JARATÍW SHEBERLIGI - Dabılov, P. (SCIENCE and SOCIETY, 2024)
In the article, the skill of creating the national character of a lyrical hero is examined using the example of the works of I.Yusupov. One of the ways to create the national character of a lyrical hero is to describe the ethnographic characteristics of the people. This issue will be revealed using the example of poems by I.Yusupov and other Karakalpak poets. As a result, the features of the formation of the poet’s national character are determined.